PENGARUH LATIHAN PERNAFASAN TERHADAP KETERAMPILAN RENANG - Ahmad Syabaruddin; Ketaren, Maulana Akhmad Shah; Habib Alfadli Nasution; Muhammad Roisuddin Hasan Siregar; M. Alfizar Zaki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Breathing exercises are one of the training methods that play an important role in improving physiological abilities and swimming skills. The purpose of this study was to analyze and summarize various national research findings regarding the effect of breathing exercises on swimming skills. The method used was a literature review by examining  national journal articles published between 2021 and 2026. The articles were obtained through searches on Google Scholar, Garuda, and various institutional repositories using keywords related to breathing exercises and swimming skills. The analysis was conducted descriptively and qualitatively using a content analysis technique. The results of the review indicate that breathing exercises have a positive impact on improving vital lung capacity, cardiorespiratory endurance, oxygen utilization efficiency, body buoyancy control, as well as movement coordination and breathing patterns during swimming. In addition, breathing exercises have been shown to reduce anxiety in the water, increase stroke efficiency, improve body position, and support enhancements in swimming speed and endurance across various swimming styles. Commonly used breathing training methods include diaphragmatic breathing, pursed-lip breathing, hypoxic training, and pranayama-based breathing exercises. Based on the synthesis of the literature, it can be concluded that breathing exercises are an effective, safe, and economical training strategy for improving swimming skills and performance. Therefore, breathing exercises are recommended to be integrated into swimming education and training programs for both beginners and competitive athletes.